1997
DOI: 10.1016/s0014-5793(97)00648-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a biological inactive complex form of pokeweed antiviral protein

Abstract: Pokeweed antiviral protein (PAP) inactivates both eukaryotic and prokaryotic ribosomes via a specific depurination of rRNA. The sensitivity of pokeweed ribosomes to PAP implies the existence of a mechanism to protect the plant. Using monoclonal antibodies specific to PAP, a protein complex (PAPi) which contained PAP was identified in leaf extract. In this complex, the enzymatic activity of the toxin was strongly inhibited. This protein complex had a p/ lower than that of PAP and was separated from free PAP by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Subdomains 1␤, 2␣, and 2␤ contain an S-S bond between the conserved Cys residues. On the other hand, the substitutions of Asn 17 and Ser 36 for Cys residues in the 1␣-subdomain rule out the formation of the standard disulfide bond. The homologous disulfide bridge is also absent in ML-I, although it is conserved in ricin, abrin, and ebulin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subdomains 1␤, 2␣, and 2␤ contain an S-S bond between the conserved Cys residues. On the other hand, the substitutions of Asn 17 and Ser 36 for Cys residues in the 1␣-subdomain rule out the formation of the standard disulfide bond. The homologous disulfide bridge is also absent in ML-I, although it is conserved in ricin, abrin, and ebulin.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have proposed the presence of natural inhibitors for RIPs also (16). The natural inhibitor of a type I RIP from Phytolacca americana, PAP, has been purified and characterized (17,18). However, no such natural inhibitor for the type II RIPs has yet been identified.…”
mentioning
confidence: 99%
“…However, it has been reported that UV induces the activation of the chalcone-synthase gene (Ohl et al 1989), and stimulates the transcription of genes involved in protective responses (Brown et al 2005), including a wide variety of antioxidant enzymes (Yannarelli et al 2006). Similarly, the UV stimulus possibly activates the transcription of curcin-L, which can form protein dimers (Desvoyes et al 1997) that absorb UV, thus weakening the UVinduced damage. In addition, curcin-L might scavenge reactive oxygen species (ROS) generated by UV, in agreement with reports that several RIPs have antioxidant activity Stirpe and Battelli 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested a possibility that this complex is a dimeric form of PAP. However, even if this complex is a dimeric form of PAP, it is unlikely to be connected by a disulphide bridge since the complex was dissociated by heating for 5 min at 80°C or by treatment by alkaline or acidic pH or by 7 M urea (34). A dimeric form of ␣-sarcin, a RIP with ribonuclease activity from Aspergillus giganteus has been identified in a purified toxin preparation (35), these dimers are enzymatically inactive and are supposed to be associated with the lowering of the cytotoxicity of ␣-sarcin (36).…”
Section: Molecular Modelling Of Cys 242 In Iripmentioning
confidence: 99%